Research handbook on copyright law - Torremans, Paul, 1965- (Research handbooks in intellectual property, 2017)
This second edition has been completely rewritten to reflect recent changes and new trends that have emerged since the popular first edition was published. Copyright law has become a fast moving area, which is reflected in the wealth and diversity of research. This comprehensive Research Handbook is situated at the cutting edge of current copyright research, with each chapter written by a leading author in that particular field. The Research Handbook begins with an examination of fundamental questions such as the historical foundations of copyright, the basic concept of originality and the significant discussion on communication to the public. The contributors then focus on moral rights and the artist resale right. In-depth treatment of specialist topics is provided, including copyright contracts, collective management, issues surrounding streaming and sampling, cultural heritage, orphan works, search engines and the potential for a public policy exclusion. The Research Handbook provides global coverage while also considering specific jurisdictions and private international law. The Research Handbook on Copyright Law is a rich research tool that reflects the wealth and diversity of the ongoing research in copyright. It is essential reading for students and researchers in copyright and intellectual property law, as well as practitioners and policymakers.